2022
DOI: 10.3389/fcvm.2022.750634
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prognostic Value of Mesenteric Artery Stenosis in Patients Undergoing Transcatheter Aortic Valve Implantation

Abstract: IntroductionData regarding the prevalence of mesenteric artery stenosis in patients undergoing transcatheter aortic valve implantation (TAVI) are scarce. Whether patients with high-risk features for acute mesenteric ischemia (AMesI) have a worse prognosis compared with those without high-risk features is unknown. We aimed to address these questions.MethodsWe included 361 patients who underwent TAVI between 2015 and 2019. Using pre-TAVI computed tomography exams, the number of stenosed arteries in each patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Furthermore, a systemic proin ammatory state during the periprocedural period may lead to an increased risk of carotid plaque rupture [13]. The same mechanisms have been used to explain, among others, the pathogenesis of acute mesenteric ischemia and acute kidney injury after TAVI [14,26]. Our analysis of the mechanisms behind the four cases of stroke in patients with CAS suggests that while unilateral CAS is possibly merely a marker of a high comorbidity (in particular vascular disease) burden, with no cerebral lesions directly attributable to it, severe bilateral CAS may indeed be a direct cause of stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a systemic proin ammatory state during the periprocedural period may lead to an increased risk of carotid plaque rupture [13]. The same mechanisms have been used to explain, among others, the pathogenesis of acute mesenteric ischemia and acute kidney injury after TAVI [14,26]. Our analysis of the mechanisms behind the four cases of stroke in patients with CAS suggests that while unilateral CAS is possibly merely a marker of a high comorbidity (in particular vascular disease) burden, with no cerebral lesions directly attributable to it, severe bilateral CAS may indeed be a direct cause of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this holds true for TAVI is currently unknown, in particular in the setting of bilateral CAS, even though a few previous studies have been published [10][11][12][13], and recent guidelines do not recommend to systematically screen for CAS before TAVI [1]. From a pathophysiological standpoint, CAS could in theory be a risk factor for ischemic neurovascular complications in patients undergoing TAVI, because the latter may induce transient hypotension and peripheral hypoperfusion via rapid ventricular pacing [14]. Using prospectively collected data from our TAVI registry, we performed the present study to (1) assess the rates of CAS -including moderate, severe or bilateral-, neurovascular complications and mortality in patients undergoing TAVI, and (2) analyze whether there is an association between CAS and the 30-day risk of stroke or TIA, as well as with 30-day all-cause mortality risk.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with another recent study examining the risk of preoperative MAS in intermediate-risk patients that demonstrated increased risk of AMI and all-cause mortality in patients with MAS in 2 or 3 mesenteric arteries. 3 Both studies suggest the presence of preoperative MAS should prompt consideration for preoperative angioplasty of the stenosed mesenteric vessels. 2,3 However, although mesenteric angioplasty can be performed with a low complication rate, these complications can be severe and life-threatening.…”
mentioning
confidence: 99%
“…3 Both studies suggest the presence of preoperative MAS should prompt consideration for preoperative angioplasty of the stenosed mesenteric vessels. 2,3 However, although mesenteric angioplasty can be performed with a low complication rate, these complications can be severe and life-threatening. 4 In fact, clinical practice guidelines from the Society for Vascular Surgery provide a weak recommendation with low level of evidence for discussing revascularization in asymptomatic patients with MAS.…”
mentioning
confidence: 99%